Barbarian's redemption eaudiobook - Dixon, Ruby (Ice Planet Barbarians, 2019)
For seasons, I have waited for her—my perfect mate. In a tribe full of happy couples, I am alone. But I am not content to remain this way. There are no eligible unmated females left, so I will do whatever it takes to bring females back to our tribe . . . even if it means doing something wrong. Even if it means I must purchase my mate on the intergalactic black market. I will do anything to possess her, to claim her as my own. But will my ruthless move turn my female against me before we ever meet? Can she ever forgive a male that bought her freedom? Contains mature themes.